Goal Attainment Scale and Clinical Efficacy Evaluation of Acupuncture - Dong LIN; Wanyu ZHUANG; Xiaozhen HUANG; Lili LIN; Qiang WU (康复学报)
Objective:To analyze the application prospect of goal attainment scale (GAS) in clinical efficacy evaluation of acupuncture, and then explore the establishment of individualized clinical assessment system of acupuncture.Methods:This article introduced a mature and individualized clinical evaluation method GAS, described its application in therapeutic efficacy assessment of acupuncture therapy in patients with mental retardation, and then analyzed the advantages and limitations of GAS.Results:Since GAS was an individualized clinical efficacy evaluation system, it could provide a good idea for the evaluation of the clinical efficacy of acupuncture.Conclusion:Through inducing GAS into clinical evaluation of acupuncture, it is possible to establish a clinical efficacy evaluation system suitable for acupuncture after repeated clinical practice and continuously improvement.